The Effect of Convenience on Customer Loyalty Through Customer Engagement and Value Co-Creation Moderation - Justin Lee (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the influence of convenience on customer engagement and loyalty, as well as the influence of customer engagement on loyalty, by considering the role of value co-creation as a moderation variable in the relationship between convenience and customer engagement. This study uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) to test the relationship between variables in the research model. Data was collected through a closed-ended questionnaire measured using a five-point Likert scale. The study population is restaurant consumers in Yogyakarta, with sampling techniques using purposive sampling. A total of 150 respondents who had visited or made purchases at restaurants in Yogyakarta were involved in this study. Data analysis was carried out using SmartPLS software through the evaluation of measurement models (outer model) and structural models (inner model). The results of the study show that convenience has a positive and significant effect on customer engagement, and convenience also has a positive and significant effect on loyalty. In addition, customer engagement has been shown to have a positive and significant influence on loyalty, and is the strongest relationship in the research model. The findings of the study also show that value co-creation plays a role as a moderator variable that strengthens the influence of convenience on customer engagement. These results indicate that ease of service supported by the customer's active participation in the process of shared value creation can increase customer engagement which ultimately strengthens customer loyalty. Therefore, companies need to create services that are easily accessible while encouraging customer engagement in the value creation process to increase customer loyalty on an ongoing basis.